(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2016)
Spironolactone (SPR) is a steroidal drug administered as a potassium-sparing diuretic for high blood pressure treatment. The drug shows incomplete gastrointestinal absorption due to its poor aqueous solubility. The physicochemical properties of SPR in crystal forms I and II suggest that differences in their aqueous solubility may lead to a lack of bioequivalence between solid-state formulations. In this study, SPR polymorphs in five batches of active pharmaceutical ingredients (APIs) from three manufacturers were characterized using powder X-ray diffraction, infrared spectroscopy, thermal analysis, and solubility measurements. SPR tablets (50 mg) were manufactured in our laboratory using API in pure form II, and API in form II contaminated with form I, which was found in a commercial batch. Physicochemical quality evaluations of the manufactured tablets, along with five SPR tablets marketed in Brazil, were performed, and results indicated differences in their dissolution profiles. In the manufactured tablets, differences were associated with the increased solubility of API in form II contaminated with form I compared to API in pure form II. In the marketed SPR tablets, the formulation composition demonstrated an important role in the dissolution rate of the drug, leading to lack of pharmaceutical equivalence among the drug products.